Assessing the Impact of Instagram on Mental Health Disorders Among Youth After COVID 19 - Peace Elizabeth Makawa (Uganda Christian University, 2024)
This dissertation examines the impact of Instagram on mental health disorders among the youth in Kampala District in the post-COVID-19 era. The study incorporates a thorough literature review, drawing from previous research on the subject, and establishes a theoretical framework to outline the research objectives. Utilizing a mixed-methods approach, the research integrates both quantitative and qualitative methods to gather comprehensive data. Data collection involved conducting surveys and in-depth interviews with youth to understand their interactions with Instagram as a social media platform. The research also includes valuable insights from medical professionals gathered through interviews conducted at three medical facilities in Kampala: Mulago Referral Hospital, Naguru Hospital, and Kairos Hospital. These facilities have treated cases relevant to the study, providing critical perspectives on the issue. The analysis of the collected data is presented in various forms, including pie charts and tables, which illustrate the statistical findings. The qualitative data offers a deeper understanding of the personal experiences and perceptions of the youth regarding Instagram's influence on their mental health. The dissertation concludes with a comprehensive discussion of the findings, highlighting the significant impact of Instagram on mental health disorders among the youth in Kampala District. Based on the results, recommendations are provided to address these issues and suggest potential interventions for improving mental health outcomes in this demographic.
Undergraduate Research